THE ALTERNATIVE BLUE OCEAN STRATEGY: BAGAIMANA STRATEGI PERUSAHAAN INDUSTRI KOPI SANTRI DALAM MENGHADAPI PERSAINGAN BISNIS? - Setiawan, Heri Cahyo Bagus; Komara, Beni Dwi (Universitas Muhammadiyah Gresik, 2020)
Companies that can survive in business competition, must use strategies that are oriented to innovative and efficient values by looking at the company resources and capabilities holistically. When the giant coffee industry companies use the red ocean strategy in the expansion of market competition, the small and medium coffee industry companies (MSMEs) such as The Coffee Santri Industry in this study take the alternative blue ocean strategy into a strategic choice. A choice of strategies that do focus differentiation. Formulating the use of the blue ocean strategy by forming a new concept, namely outlet treatment, coffee shop and manufacturing scrubs, aroma therapy and prayer coffee are essential for survival and expansion outside the Red Ocean arena.